The Effect of Entrepreneurship Knowledge and Motivation on Business Successs through Self-Efficacy on MSMEs Activities in the City of Jember - Sapta Yanuar; Diana Sulianti K. Tobing; Ika Barokah Suryaningsih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aims of the study are to find out the effect of entrepreneurship knowledge and motivation on business successs through self-efficacy on msmes activities in the city of jember. This study uses quantitative research Method. The result shows that Entrepreneurial knowledge and motivation had a direct effect on business successs by 0.343 and 0.419., Entrepreneurial knowledge had indirect effect on business success through self-efficacy by 0.011 so the total effect was 0,354. Motivation has an indirect effect on business success through self-efficacy by 0.062 so the total effect was 0,481.